PENGARUH TERAPI SENAM AEROBIK LOW IMPACT TERHADAP TINGKAT DEPRESI PADA PASIEN SKIZOFRENIA DI RSJD DR. RM. SOEDJARWADI PROVINSI JAWA TENGAH - Ngapiyem, Ruthy; Kumala Sari, Agnes Lisa (STIKES Bethesda Yakkum, 2018)
Background : The study was based on a preliminary study in the form of observations and interviews to patients hospitalized in room RSJD. Dr. RM. Soedjarwadi Central Java Province, which found 178 inpatientsdiagnosed with schizophrenia. Objective : This study aimed to determine the effect of depressed patients with schizophrenia before and after treatment in low impact aerobics RSJD. Dr. RM. Soedjarwadi Central Java Province. Methods : The sampling technique used was purposive sampling with 19 respondents. Quasi Experiment design used to design one group pretest-posttest design. The analysis used Paired Wilcoxon Match Paired Test. Results : Wilcoxon Match Pair Test for levels of depression before and after therapy exercises signifcant values obtained value of 0.000 (p <0.05). Conclusion : Based on this study obtained p <? = Ho rejected and accepted H? means no therapeutic effect of low impact aerobicgymnastics on the level of depression in patients with schizophrenia in RSJD. Dr. RM. Soedjarwadi Central Java province in 2016. Suggestion : To apply a low impact aerobic exercise therapy in RSJD. Dr. RM.Soedjarwadi Central Java province as one of the interventions to reduce the level of depression in patients with schizophrenia.Keywords: Gymnastics Therapy - Depression – Schizophrenia